Treinamento suspenso vs. treinamento de força tradicional: efeitos na massa muscular, força e desempenho funcional em idosos - Soligon, Samuel Domingos (2020)
Purpose We compared the effects of suspension training (ST) with traditional resistance training (TRT) on muscle mass, strength and functional performance in older adults. Methods Forty-two untrained older adults were randomized in TRT, ST (both performed 3 sets of whole body exercises to muscle failure) or control group (CON). Muscle thickness (MT) of biceps brachii (MTBB) and vastus lateralis (MTVL), maximal dynamic strength test (1RM) for biceps curl (1RMBC) and leg extension exercises (1RMLE), and functional performance tests (chair stand [CS], timed up and go [TUG] and maximal gait speed [MGS]) were performed before and after 12 weeks of training. Results MTBB increased significantly and similarly for all training groups (TRT: 23.35%; ST: 21.56%). MTVL increased significantly and similarly for all training groups (TRT: 13.03%; ST: 14.07%). 1RMBC increased significantly and similarly for all training groups (TRT: 16.06%; ST: 14.33%). 1RMLE increased significantly and similarly for all training groups (TRT: 14.89%; ST: 18.06%). MGS increased significantly and similarly for all groups (TRT: 6.26%; ST: 5.99%; CON: 2.87%). CS decreased significantly and similarly for all training groups (TRT: -20.80%; ST: -15.73%). TUG decreased significantly and similarly for all training groups (TRT: -8.66%; ST: -9.16%). Conclusion ST promotes similar muscle mass, strength and functional performance improvements compared to TRT in older adults.